The Effect of High-Pressure Homogenization Conditions on the Physicochemical Properties and Stability of Designed Fluconazole-Loaded Ocular Nanoemulsions - Agnieszka Gawin-Mikołajewicz; Urszula Nawrot; Katarzyna Hanna Malec; Karolina Krajewska; Karol Przemysław Nartowski; Bożena Lucyna Karolewicz (MDPI AG, 2023)
The growing interest in high-energy emulsification is a result of its scalability, which is important from an industrial perspective and allows for a more reproducible and efficient production of pharmaceutical formulations. The aim of this study was to evaluate the effect of composition, mainly a fixed surfactant/cosurfactant (Smix) ratio, their concentration, and the parameters of high-pressure homogenization (HPH) processing on the quality and stability of ophthalmic fluconazole-loaded nanoemulsions. After a physicochemical analysis of nanoemulsions containing 20% w/w of oil, as optimal conditions for the HPH process, three cycles at a pressure of 1000 bar were established, obtaining formulations with an average droplet diameter size in the range of 80.63-129.68 nm and PDI values below 0.25. While it was expected that an increasing cosurfactant concentration decreased the droplet size, in the case of formulations containing Tween 20 and 10% w/w of cosurfactants, "over-processing" was observed, identified by the droplet size and polydispersity index increase. Consecutively, the selected formulations were evaluated for in vitro drug release in Franz's cell, antifungal activity, and 30-day stability using NMR spectroscopy. An antifungal activity test showed no significant difference in the antifungal activity between optimal fluconazole-loaded nanoemulsions and a 0.3% aqueous drug solution, but previously, research showed that prepared formulations were characterized by a higher viscosity and satisfactory prolonged release compared to a control. In a 30-day stability study, it was observed that higher HLB values of the used surfactants decreased the stability of the formulations in the following order: Kolliphor EL, Tween 80, Tween 20. The NMR spectra confirmed that Kolliphor EL-based formulations ensured the higher stability of the nanoemulsion composition in comparison to Tween 80 and a better stabilizing effect of propylene glycol as a cosurfactant in comparison to PEG 200. Therefore, the optimization of HPH technology should be focused on the selection of Smix and the Smix:oil ratio in order to prepare stable formulations of high quality.